An unusual eukaryotic protein phosphatase required for transcription by RNA polymerase II and CTD dephosphorylation in S. cerevisiae. - Kobor, MS; Archambault, J; Lester, W; Holstege, F; Gileadi, O; Jansma, D; Jennings, E; Kouyoumdjian, F; Davidson, A; Young, R; Greenblatt, J (1999)
The carboxy-terminal domain (CTD) of the largest subunit of RNA polymerase II is phosphorylated soon after transcriptional initiation. We show here that the essential FCP1 gene of S. cerevisiae is linked genetically to RNA polymerase II and encodes a CTD phosphatase essential for dephosphorylation of RNA polymerase II in vivo. Fcp1p contains a phosphatase motif, psi psi psi DXDX(T/V)psi psi, which is novel for eukaryotic protein phosphatases and essential for Fcp1p to function in vivo. This motif is also required for recombinant Fcp1p to dephosphorylate the RNA polymerase II CTD or the artificial substrate p-nitrophenylphosphate in vitro. The effects of fcp1 mutations in global run-on and genome-wide expression studies show that transcription by RNA polymerase II in S. cerevisiae generally requires CTD phosphatase.